Saccharin: a cheap and mild acidic agent for the synthesis of azo dyes via telescoped dediazotization - Khaligh, Nader Ghaffari; Johan, Mohd Rafie; Juan, Joon Ching (De Gruyter, 2019)
Green synthesis methods are considered as a safer alternative to the conventional synthetic processes due to their eco-friendly nature, cost-effectiveness, and easy handling. In the present study, an eco-friendly and sustainable method for the synthesis of stable arenediazonium has been developed using saccharin as a cheap and mild acidic agent and tert-butyl nitrite as a diazotization reagent for the first time. These stable intermediates were used in the azo coupling reaction with 4-hydroxybenzaldehyde via telescoped dediazotization. The current method has advantages such as reduced waste by avoiding solvent for the purification of intermediate in diazotization step, cost-effectiveness, simple experimental procedure, good yield of azo dyes, metal-free waste, and environmentally benign conditions. An interesting aspect of this study is the recovery of saccharin from the reaction, which could be reused. © 2019 Walter de Gruyter GmbH, Berlin/Boston.